2014
DOI: 10.1186/alzrt251
|View full text |Cite
|
Sign up to set email alerts
|

Lewy body dementia: the impact on patients and caregivers

Abstract: Lewy body dementia (LBD) is the second most common neurodegenerative dementia in older adults, yet there remains a delay in diagnosis that limits healthcare providers’ ability to maximize therapeutic outcomes and enhance patient and caregiver quality of life. The impact of LBD on patients includes limiting the potential exposure to medications that may cause adverse outcomes, and addressing how the disease manifestations, such as autonomic features and behavior, affect quality of life. LBD impact on caregivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 35 publications
5
63
0
1
Order By: Relevance
“…20 A previous study also reported that 26% of DLB patients were initially misdiagnosed with AD, and 57% of these DLB patients presented with memory impairment. 21 We Abbreviations : understand that an accurate diagnosis of DLB is very important for subsequent management. Patients with DLB are particularly sensitive to neuroleptics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 A previous study also reported that 26% of DLB patients were initially misdiagnosed with AD, and 57% of these DLB patients presented with memory impairment. 21 We Abbreviations : understand that an accurate diagnosis of DLB is very important for subsequent management. Patients with DLB are particularly sensitive to neuroleptics.…”
Section: Discussionmentioning
confidence: 99%
“…21 Neuroleptic sensitivity can present as drowsiness, confusion, abrupt worsening of parkinsonism, postural hypotension, or neuroleptic malignant syndrome. 21 Other clinical features of DLB that need to be observed and tackled include well-formed visual hallucinations, rapid eye movement sleep behavioural disorder, and autonomic symptoms (including postural hypotension, sialorrhoea, and urinary and bowel symptoms). 21 By accurately establishing the diagnosis of DLB, careful observation of classic DLB symptoms may reduce unnecessary investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to nursing home placements, hospitalisation triggers a high cost profile for care and often leads to longer term placement in residential care. For people with dementia hospitalisation is undesirable as it is associated with a worsening of cognition and the emergence or worsening of neuropsychiatric symptoms, which are often managed with antipsychotic medications 57 . An additional risk in people with DLB is the misdiagnosis and mismanagement of delirium 58 .…”
Section: Hospitalisationmentioning
confidence: 99%
“…Az LBDA felmé-rése alapján átlagosan négy orvost keres fel a beteg, mire a DLB kórismézésre kerül, 31%-ban pedig két év után sincs helyes diagnózis [76]. Az esetek 78%-ában az első diagnózis hibás, legtöbbször PD-vel (39%), AD-vel (26%) vagy valamilyen primer pszichiátriai kórképpel (24%) tévesztik össze [77].…”
Section: Következtetésekunclassified